Oil and the political economy in the Middle East post-2014 adjustment policies of the Arab Gulf and beyond - Beck, Martin, 1962 October 23-; Richter, Thomas (Manchester University Press, 2021)
This is the first comprehensive analysis of the Middle East political economy in response to the oil price decline in 2014. Based on a heuristic framework inspired by rentierism, the volume contains original studies on Bahrain, Egypt, Jordan, Kuwait, Lebanon, Oman, Qatar, Saudi Arabia, and the United Arab Emirates.